FEATURES OF THE PHYTOCHEMICAL COMPOSITION OF THYMUS TAURICUS (LAMIACEAE) ESSENTIAL OIL DURING THE INTRODUCTION IN THE FOREST-STEP OF UKRAINE - КОВТУН-ВОДЯНИЦЬКА, Світлана; ЛЕВЧУК, Ірина; ГОЛУБЕЦЬ, Ольга; РАХМЕТОВ, Джамал (ВПЦ "Київський університет" - Publishing center "Kyiv University", 2025)
Backgrround. Natural essential oils (EOs) are currently in high demand on the world market and are an area of significant positive financial effect. However, in Ukraine, the state of research and introduction into culture of new, primarily autochthonous species, requires stimulation and interest from domestic EO producers, which are currently few. In this work, we aimed to investigate the EO potential of Thymus tauricus Klokov & Des.-Shost. (Lamiaceae), as an aboriginal species introduced in the conditions of the M. M. Gryshko National Botanical Garden of the NAS of Ukraine (Right-Bank Forest-Steppe) and to outline the prospects for practical use as a raw material crop. Methods. In laboratory studied the aerial herbaceous part of Th. tauricus. Raw materials were harvested in the flowering phase of plants. EO was isolated by hydrodistillation. Analysis of oil components was performed by gas chromatography with mass spectrometric detection (GC-MS). Results. The EO content in the above-ground part of Th. tauricus is 1,91-2,66%. It identified 70 compounds and determined their quantitative content. The dominant ones are linalyl acetate (19,6%), linalool (18,3%), α-terpinyl acetate (13,4%), carvacrol (12,4%), ρ-cymene (4,2%) and others. They exhibit a diverse pharmacological effect on the human body, in particular antioxidant, anti-inflammatory, antidiabetic, antiviral, antitumor, antibacterial, etc. In general, the phytochemical composition of EO Th. tauricus determines the practical use of plant raw materials of this species, volatile oil and its individual compounds. Conclusions. The EO content in the raw material of introduced plants Th. tauricus, as well as the qualitative and quantitative component composition, was determined. The dominant compounds determine its potential pharmacological action, which should be studied in more detail in practice. The plants represent an interesting chemical phenotype for further biochemical, ecological studies and practical breeding work.

Вступ. Натуральні ефірні олії (ЕО) на сьогодні користуються високим попитом на світовому ринку і є сферою неабиякого позитивного фінансового ефекту. Проте, в Україні стан дослідження та впровадження в культуру нових, насамперед автохтонних ефіроолійних видів рослин, потребує стимуляції та зацікавленості з боку вітчизняних виробників ЕО, які на сьогодні нечисленні. У даній роботі ми мали за мету дослідити ефіроолійний потенціал Thymus tauricus Klokov & Des.-Shost. (Lamiaceae), як аборигенного виду, інтродукованого в умовах Національного ботанічного саду імені М.М. Гришка НАН України(Правобережний Лісостеп) та окреслити перспективи практичного використання як сировинної культури. Методи. У лабораторних дослідженнях використано надземну тра`яну частину Th. tauricus, Заготівлю сировини проведено у фазу квітування рослин. ЕО виділено методом гідродистиляції. Аналіз складників олії – методом газової хроматографії з мас-спектрометричним детектуванням (ГХ-МС). Результати. Вміст ЕО у надземній частині Th. tauricus становить 1,91-2,66%. У ній ідентифіковано 70 сполук, встановлено їх кількісний вміст. Домінантними є ліналіл ацетат (19,6%), ліналоол (18,3%), α-терпінил ацетат (13,4%), карвакрол (12,4%), ρ-цимен (4,2%) та інші. Вони виявляють різнобічну фармакологічну дію на організм людини, зокрема антиоксидантну, протизапальну, антидіабетичну, противірусну, протипухлинну, антибактеріальну тощо. У цілому фітохімічний склад ЕО Th. tauricus обумовлює практичне застосування рослинної сировини даного виду, леткої олії та окремих її сполук. Висновки. Визначено вміст ЕО у сировині інтродукованих рослин Th. tauricus, а також якісний та кількісний компонентний склад. Домінуючі сполуки визначають її потенційну фармакологічну дію, що доцільно поглиблено вивчити у подальшому на практиці. Рослини представляють цікавий хімічний фенотип для біохімчних, екологічних досліджень та практичної селекційної роботи.
ФІТОХІМІЧНА ХАРАКТЕРИСТИКА ЕФІРНОЇ ОЛІЇ THYMUS TAURICUS (LAMIACEAE) ЗА ІНТРОДУКЦІЇ У ЛІСОСТЕПУ УКРАЇНИ
Keywords: Thymus tauricus; essential oil; gas chromatography; chemical phenotype; Key words: Thymus tauricus; essential oil; gas chromatography; chemical phenotype; Thymus tauricus; ефірна олія; газова хроматографія; хімічний фенотип; Thymus tauricus; ефірна олія; газова хроматографія; хімічний фенотип